One Stop Integrated Service Management at Madrasah Tsanawiyah Negeri 2 Bondowoso - W.S, Edent Alfin Nur; Ummah, Nur Ittihadatul (Rausyan Fikri Journal of Islamic Studies, 2024)
The purpose of this article is to describe how these four aspects are applied in an effort to improve the efficiency and quality of services. The approach used in this study is qualitative with a case study method. Data was collected through observation, interviews, and documentation, then analyzed using an interactive analysis model. The validity of the data is guaranteed through triangulation of techniques and sources. The results of the study show that: 1) Planning is carried out by establishing policies through a Decree by the head of the madrasah, supported by the preparation of SOPs by the head of TU as a work guideline. 2) Organizing includes three forms of service: a) Oral, in the form of information conveyed in a friendly and clear manner; b) Writing, in the form of orderly and accurate management of official documents; c) Acts, in the form of direct service by officers with a friendly, empathetic, and professional attitude. 3) Implementation is improved through the implementation of the Srikandi application which facilitates coordination, archiving, and monitoring services in real-time according to SOPs. 4) The evaluation was initially done manually using the suggestion box, then switched to an online complaint system through the Srikandi app, which increased the transparency and effectiveness of service monitoring. This study concludes that the implementation of digital-based PTSP in MTsN 2 Bondowoso is able to increase the efficiency, transparency, and accountability of education administration services.